Variasi persen berat tempurung kelapa terhadap konduktivitas termal komposit silicone rubber - Mirmanto, M.; Sugiman, S.; Ramadhani, M.D.; Fathurrahman, F. (Dinamika Teknik Mesin, 2021)
Experiments to know themal conductivities of silicone rubber composite were conducted. The sillicon rubber was mixed with coconut shells charcoal powder with weight variations. The weight presentage variations were 0, 10, 20 and 30%. Increasing the weight persentage was expected to increase the thermal conductivity of the composite. The speciment size was 50 mm x 50 mm x 5 mm. The speciments were tested according to the conduction heat transfer mode. To make sure that the temperatures were steady, the experiments were performed for about 6 hours. The results indicated that increasing the weight presentage raised the composite thermalconductivities. At 0% of wight, the composite had a thermalconductivity of 0.157 W/m°C, at 10%, 20% and 30% of weight compositions; the composite had thermal conductivities of 0.461 W/m°C, 0.58 W/m°C, and 0.73 W/m°C respectively.